Assessment of Ginintuang Masaganang Ani corn program cooperators in Siquijor Province - Macalino, Pilar P. (University of the Philippines Visayas, 2005)
This study was conducted to assess the effectiveness of the Ginintuang MasaganangAni (GMA) Corn Program in increasing the production and level of income of the farmers in Siquijor Province. Data collection was done through a survey and it was analyzed using descriptive statistics. The results of the study showed that majority of the respondents were female aged 41 to 50 years, high school graduates, Roman Catholic, and with an average family members of five. Farming was their major source of income earning below P3,000 a month. They were dwelling in semi-permanent housing and tilling less than three hectares of land for almost 16 years as shared tenants. Out of this area, they devoted less a hectare for corn production which was self-financed. Furthermore, the program was effective in disseminating information through training and enhanced learning of farmers, while most have planted hybrid corn seeds, others still use of the traditional seeds which they intend to store for consumption. The Integrated Pest Management (IPM) approach and other cultural practices. Effective to covered the infestations of crops that are environment friendly were also practiced in the farm. There was an increase in any level of corn production before and after the program as reported by part of respondents. They also observed corresponding increase in capitalization by the margin derived was higher several times over what they had before the program. In general the farmers were satisfied of the new farming techniques and are now practicing them on their own farms. The GMA Corn program was effective in giving learning experiences and insights that made farmers earn more and uplift their economic level of living. Farmers can now send their children to school without much worry about their expenses, can buy simple appliances in cash, and other necessities in life which they did not achieve before. As to their way of spending their leisure time, the farmers can spend their leisure going to movies or go on shopping through majority still prefer to stay at home. Desite the advantages or benefits they got from the program, they also encountered difficulties during the process such as the conflicting time of consultation, unavailability of the farm technician, inadequate capitalization, and insufficient inputs received. As a whole, the program as perceived by the farmers was effective in increasing their income and production hence, uplift their standard of living.